Ionic dissolution products of Cerium-doped bioactive glass nanoparticles promote cellular osteogenic differentiation and extracellular matrix formation of human bone marrow derived mesenchymal stromal cells - Westhauser, Fabian; Rehder, Felix; Decker, Simon; Kunisch, Elke; Moghaddam-Alvandi, Arash; Zheng, K.; Boccaccini, Aldo R. (Biomedical materials, 2021)
Cerium (Ce) is a promising candidate ion for application in bone tissue engineering (BTE) since it reduces the presence of reactive oxygen species. Ce-doped mesoporous bioactive glass nanoparticles (MBGNs) serving as vectors for the local application of Ce already demonstrated stimulating effects on the expression of pro-osteogenic genes in Saos-2 cells. So far, there is no evidence available about the effects of Ce-doped MBGNs on the viability, osteogenic differentiation and the formation of the osseous extracellular matrix (ECM) of primary human bone marrow-derived mesenchymal stromal cells (BMSCs). Therefore, in this study, the biocompatibility of the ionic dissolution products (IDPs) of MBGNs containing increasing concentrations of CeO2 (0.05 MCe-MBGNs, composition in mol%: 86.6SiO2-12.1CaO-1.3CeO2; and 0.2 MCe-MBGNs, composition in mol%: 86.0SiO2-11.8CaO-2.2CeO2) and unmodified MBGNs (composition in mol%: 86SiO2-14CaO) was evaluated using human BMSCs. Eventually, the impact of the MBGNs’ IDPs on the cellular osteogenic differentiation and their ability to build and mature a primitive osseous ECM was assessed. The Ce-doped MBGNs had a positive influence on the viability and stimulated the cellular osteogenic differentiation of human BMSCs evaluated by analyzing the activity of alkaline phosphate as a marker enzyme for osteoblasts in the present setting. Furthermore, the formation and calcification of a primitive osseous ECM was significantly stimulated in the presence of Ce-doped MBGNs in a positive concentration-dependent manner as demonstrated by an elevated presence of collagen and increased ECM calcification. The results of this in-vitro study show that Ce-doped MBGNs are attractive candidates for further application in BTE.